Measurement report: Analysis of aerosol optical depth variation at Zhongshan Station in Antarctica - L. Chen; L. Chen; L. Zhang; Y. She; Z. Zeng; Y. Zheng; B. Tian; W. Zhang; Z. Liu; H. Che; M. Ding (Atmospheric Chemistry and Physics)
Our understanding of aerosol optical depth (AOD) in Antarctica remains limited due to the scarcity of ground observation stations and limited daylight days. Utilizing data from the CE318-T photometer spanning January 2020 to April 2023 at Zhongshan Station, we analyzed the seasonal, monthly, and diurnal variations in AOD and the Ångström exponent (AE). AOD median values increased from spring (0.033) to winter (0.115), while AE peaked during summer (1.010) and autumn (1.034), declining in winter (0.381), indicating a transition in dominant aerosol particle size from fine to coarse mode between summer and winter. Monthly mean AOD variation closely paralleled the proportion of AE < 1, suggesting fluctuations in coarse-mode particle proportions drive AOD variation. The high AOD values during winter and spring were associated with an increased contribution of coarse-mode particles, while high AOD values during summer and autumn were associated with the growth of fine-mode particles. We observed a peak in AOD (∼ 0.06) at 14:00 local time (LT) at Zhongshan Station, possibly associated with a slight decrease in boundary layer height (BLH). Additionally, higher (lower) wind speeds corresponded to lower (higher) AOD values, indicating the diffusion (accumulation) effect. The temperature and AOD showed an insignificant positive correlation (R = 0.22, p = 0.40), and relative humidity exhibited a significant negative correlation with AOD (R = −0.59, p = 0.02). Backward trajectory analysis revealed that coarse particles from the ocean predominantly contributed to high AOD daily mean values, while fine particles on low-AOD days originated mainly from the air mass over the Antarctic Plateau.